Psychometric properties and invariance of the scale to measure attitude of researchers for university-industry collaboration - Pérez-Morán, Juan Carlos; Morales-Páez, Marcela; Bernal-Baldenebro, Brandon; Cano-Gutiérrez, Julio César (Frontiers in Education, 2023)
The psychometric properties of the Scale to measure the attitude of researchers for scientific-technological collaboration between universities and industry (EA-COOPTEC, for its acronym in Spanish) were analyzed, specifically evidence of construct validity of the internal structure and invariance for gender and age was obtained. The EA-COOPTEC was administered to 179 academic Teachers–Researchers (T-Rs) involved in Universities-Industry Collaboration (UIC) activities: 50 female and 129 male. Participants had a median age of 36-40 years. A descriptive analysis was implemented, as well as an Exploratory and Confirmatory Factor Analysis (EFA and CFA), and a method of succession of nested models for invariance testing. A four-factor model explaining the perception of UIC activities was generated and evidence of invariance for gender and partial invariance for age was obtained. Acceptable fit indices were obtained for the configurational, weak, strong and strict. Given the results, we recommend the use of the EA-COOPTEC v0.1 for the analysis of the mean differences between genders and age in T-Rs.